Right-handed neutrinos, domain walls and tadpoles in the superstring inspired μνSSM - Lopez, Daniel Elbio (2023)
We discuss the special role of right-handed neutrinos in the μνSSM for solving the μ- and ν-problems, simultaneously avoiding the potential domain wall and tadpole problems. In particular, embedding the μνSSM in the framework of superstrings implies that not all gauge invariant terms are necessarily present in the superpotential, and thus there is more flexibility to allow only those that avoid the domain wall and tadpole problems to be present. These can be non-renormalizable terms of dimension 4 or terms of higher dimensions. In addition, non-perturbative effects can also solve both problems. We discuss another implication of the superstring inspired μνSSM, since the right-handed neutrino is expected to have extra U(1) charges at high energies. In this case, the cubic right-handed neutrino terms in the superpotential, helpful for generating Majorana masses and solving domain wall and tadpole problems, can arise through a variety of stringy mechanisms.